Sustainability in focus: From management to environmental legislation in Brazil - Pereira, William Marques; Nunes , Elen Rosa dos Reis; Santos, Giovanna Parisi Cabeça; Rodrigues, Zelinda Duarte; Vieira, Layane de Souza; Nunes, Tiago da Silva; Moreira , Auricilene Gomes; Melo , Felipe Cristian Neves de (Seven Editora, 2024)
The present work aims to analyze the management and its environmental dimension through the premises of sustainability, bringing in this context the importance of legislation relevant to the environment. Thus showing that the legal frameworks referring to the place where life develops in the territory are supported by the Federal Constitution and other various legislations. This research was built from bibliographic studies and documentary analysis in works by the main authors on the relationship management-sustainability-legislation, under a complex view. In this way, a more detailed analysis of the subject is produced, in the search for an understanding of this relationship, showing the importance of environmental licensing in Brazil. DOI:https://doi.org/10.56238/sevened2023.006-126